Nanoclay-mediated photocatalytic activity enhancement of copper oxide nanoparticles for enhanced methyl orange photodegradation - Khan, Idrees; Khan, Ibrahim; Usman, Muhammad; Imran, Muhammad; Saeed, Khalid (Journal of materials science. Materials in electronics, 2020)
Photodegradation of organic pollutants is considered to be the most suitable and cheaper techniques to counter the contamination issues. Metal nanoparticles are considered to be the most effective heterogenous photocatalysts for the photodegradation of organic pollutants. Besides, CuO oxide nanoparticles are well-known photocatalysts for photocatalytically degrading organic pollutants. Herein, we reported the synthesis of pure copper oxide nanoparticles (CuO NPs) and nanoclay-supported copper oxide nanoparticles (CuO/NC NPs) by facile chemical reduction technique for swift photodegradation of organic dye. The X-ray diffractogram (XRD) has demonstrated a typical monoclinic phase of CuO NPs. The morphological features via scanning electronic microscopy (FESEM) showed agglomerated morphology of CuO NPs with 372.57 ± 1.76 nm average particle size. The micrographs also revealed the homogenous dispersion of CuO NPs over NC surface in CuO/NC nanocomposite. A polydispersity index (PDI) of 0.39 presented slight variation in the particle size of CuO NPs, which is also supported by the results obtained from atomic force microscopy (AFM), FESEM and transmission electron microscopy (TEM). CuO/NC NPs demonstrated outstanding methyl orange degradation over a very short period of time under simulated light. Using CuO/NC NPs, about 97.18% and 95.96% dye degradations were achieved in merely 4 min, under UV and visible light, respectively. The excellent photodegradation efficacy of CuO/NC NPs can be attributed to the homogenous distribution of CuO NPs, which facilitates the generation of photoexcitons (electrons and holes), enhances charge transfer and minimizes the charge recombination. The NC induced the required photostability by providing sufficient space for NPs distribution.